A literature review of financial contracting theory from the Islamic and conventional overviews: contributions, gaps, and perspectives - Ajmi, Hechem; Kassim, Salina; Abd Aziz, Hassanuddeen; Mansour, Walid (King Abdulaziz University Scientific Publishing Center, 2019)
This paper discusses the financial contracting theory from the conventional and Islamic perspectives. It provides an overview of the contributions in this field and discusses the gaps in the literature. In addition, it proposes two relevant approaches namely the financial contracting enforceability approach and the adverse selection analysis in order to deal with conflicts of interest among economic agents. The first approach is meant to assess the contract that maximizes the value of the firm subject to the enforcement constraint for the agent and the participation constraint for the principal. The second approach considers an adverse selection framework in order to determine the principal’s subjective perception of the risk of default when equity and debt financings are used. Similarly, it suggests avenues for future research. Firstly, it calls for a deeper understanding of venture capital as a potential model of mushārakah. Secondly, it puts stress on the importance of examining crowd-funding functioning from the principal-agent point of view. Thirdly, it sheds some light on the necessity to yield financial explanation about the excessive use of murābaḥah instead of ijārah. In a nutshell, we assume that the alternative approaches can be adopted to provide relevant insights regarding the proposed future researches.